Pengaruh Media Pembelajaran Pop-Up Book terhadap Motivasi Belajar pada Pembelajaran IPA Materi Ekosistem Lahan Basah Kelas 3 SD Muhammadiyah 07 Medan - Fani Handini Riana; Lilik Hidayat Pulungan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to see how pop-up books influence the desire to study science subjects on wetland ecosystems in class 3 at SD Muhammadiyah 07 Medan. The type of quantitative research used in this research is a quasi-experimental control group design. This research took two classes as samples, with one class being the class that used pop-up books as a learning medium and the other class not using pop-up books as a learning medium. The sampling technique uses cluster random sampling in sampling and uses a questionnaire for data collection of 20 items. To analyze the data, the T test was used which has been used previously for the Shapiro Wilk normality test and Levene's homogeneity test. Before the research began, a reliability test was carried out using Cronbach's alpha and a validity test using the Gregory formula. Test the hypothesis using the T test, which has a significance value of 0.000. Based on the findings obtained, it is concluded that pop-up books have an important influence on student learning motivation at SD Muhammadiyah 07 Medan. This could be one solution for making pop-up books as a learning medium as an alternative. to increase students' motivation to learn.